Mardhatillah as The Main Purpose of Islamic Education - Ade Arip Ardiansyah; Nurwadjah Ahmad EQ; Andewi Suhartini (Matan : Journal of Islam and Muslim Society, 2022)
Happiness is the ultimate purpose of human life that is manifested in people’s efforts to reach mardhatillah. This research is qualitative research and library research. The result showed that mardhatilah is the main purpose of Islamic education since educated people are those who are endowed with God’s pleasure. Islamic education intends to educate people on a real identity as a loving people who are not only committed to worshiping God but also able to build social-harmony life.